La philosophie de la renaissance : Bruno, Campanella, Paracelse, Boehme, Bacon, Galilee, Kepler, Newton, Machiavel, Bodin, Grotius, Hobbes, Vico - Bloch, Ernst (Paris : Payot, 1974)
Bibliotheek François Vercammen
Frans
Monografie
Keywords: filosofie